Jehovah's Witnesses - Candeias, Pedro (1999)
This article follows the article published in this magazine, Vol. 4, Nº 1, 1997, p. 56-59, titled "]ehovah's Witnesses - Comments on the Refusal of hemotherapy". Not considering matters of theological nature which are not connected with the blood issue, this article try to clarify the position of Jehovah's Witnesses in connection with transfusion therapy, in the legitimate exercise of the right of "informed consent". Is considered ethico-legal aspects and how the medico-surgical challenge of treating without allogeneic blood has been faced with success, as documented in medical literature. Additionaly it is also observed the appearing of hospital facilities in many countries, specialized in medico-surgical allogeneic nonblood management. Also considered is the functioning of Hospital Information Services (HIS) a structure of support.